DNA Mutation Induced Toxicity - Stevanovic, Radmila M. (Jour Med Resh and Health Sci, 2024)
Mutation are hereditary changes in genetic information, resulting from spontaneous or xenobiotic induced DNA damage. The number of proto-oncogenes that must be activated to convert a normal cell into a malignant cell is unknown at present. Point mutation and frame shift mutations were examined. Phosphorylation is the most important in the synthesis of purine and pyrimidine nucleosides and DNA damage. Impact of toxic effects to phosphorylation reactions modifications and xenobiotic inducing was studied. In this paper a normal cell into a malignant cell transformation was considered